Evaluating Water Safety: A Study of Microbial Contaminants in Mobile Tanks in Basrah City/Iraq - Alkanany, Fadhil F.; Gmais , Satar A.; Jaafar, Abdulridha A. (Mesopotamian Journal of Marine Sciences, 2025)
This study assessed the microbial and physico-chemical quality of water stored in mobile tanks across Basrah governorate, Iraq, to evaluate possible health threats associated with their use for drinking and domestic purposes. Twenty water samples were gathered and tested for total plate count, total coliforms, fecal coliforms, total dissolved solids (TDS), electrical conductivity (EC), and pH. The findings exposed significant microbial contamination, with total plate counts reaching up to 103 CFU/100 mL, average total coliforms of 27.4 CFU/100 mL, and fecal coliforms averaging 2.3 CFU/100 mL, demonstrating fecal contamination and paired with health risks. Physico-chemical parameters showed mild ionic content (mean TDS 61.5 mg/L, EC 92.3 µS/cm) and slightly alkaline pH (7.0–7.6), conditions favorable to microbial survival. Higher contamination correlated with infrequent tank cleaning and environmental factors such as sunlight exposure and temperature. These outcomes highlight the urgent requirement for regular water quality monitoring, enhanced tank maintenance, effective disinfection, and public education to conserve health in societies that adopt on mobile tank water supplies in Basrah as a drinking source.